Health status of coral reef at Moramo Bay Marine Conservation Area, Southeast Sulawesi, Indonesia - DEDY OETAMA; LUCHMAN HAKIM; TRI D. LELONO; MUHAMMAD MUSA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Oetama D, Hakim L, Lelono TD, Musa M. 2024. Health status of coral reef at Moramo Bay Marine Conservation Area, Southeast Sulawesi, Indonesia. Biodiversitas 25: 1454-1464. Moramo Bay is one of the regional Marine Conservation Areas (MCA) in Indonesia which is categorized as a Marine Tourism Park based on the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 22 of 2021. This bay is located in Southeast Sulawesi Province and has an area of 21,902.34 ha, consisting of a core zone, limited-use zone, and other zones. The ecosystems found in Moramo Bay include coral reefs, mangroves, and seagrass. The coral reef ecosystem in this area covers 2,528.19 ha with good visual conditions of the reef. The present study aims to provide detailed information concerning the condition of live hard corals and reef fishes, including abundance, diversity, evenness, dominance, and water quality by using point intercept transect (PIT) and underwater visual census (UVC) methods. The study was carried out at 7-10 meters of seawater depth in May-October 2023, focusing on both the core and limited-use zones and consisting of three study stages: field observation, data collection, and data analysis. Data collection covered identifying coral growth through literature study before performing descriptive analysis. The study revealed the percentage of live hard coral cover of 53%, referred to as a good category, and other variable percentages including dead coral (4%), dead coral with algae (9%), soft coral (4%), fleshy seaweed (1%), rubble (17%), sand (8%), silt (1% ) and sponge (2%). Furthermore, 25 families of reef fishes were found, belonging to 48 genera, 102 species, and 2,364 individuals, with an ecological index of abundance of 1.05 ind.m-2, diversity (2.86), evenness (0.83), and dominance (0.10). The coral reef health data issued by the present study implies that Moramo Bay MCA may be preserved as an alternative area for coral reef studies associated with global issues, for instance, climate changes. Protecting and increasing the sustainability of coral reefs is an absolute entity that must be considered by a local government.